CLASSICAL 1D LINEAR MODELS FOR INFRARED ABSORPTION AND ESTIMATES FOR THE VIBRATIONAL AMPLITUDES AND ENERGY OF NaCl IONIC COMPOUND - Jorge Corrêa de Araújo; Rosa María García Márquez (Química Nova)
Sodium chloride, NaCl, was analyzed using two models based in classical physics with the main objective of verifying whether this ionic crystal is active or not to infrared absorption. The results from the first reduced mass linear diatomic model (RMLDM) which uses the concept of reduced mass, showed that NaCl is inactive in infrared radiation. In contrast, the linear diatomic model (LDM) indicated that from a theoretical point of view there may be a weak or even insignificant absorption in the vibrational bands ν̅ ≅ 1524 and 1421 cm-1 with the amplitudes of these ionic molecular vibrations varying between 5.5 × 10-12 and 9.5 × 10-12 m. Furthermore, the LDM model developed here in this study, combines elementary equations from classical physics with elements from quantum physics enabling to estimate the energy absorption of the NaCl and also the ions sodium and chloride with good accuracy. This model can be applied, in principle, to other diatomic molecules as a good approximation to molecular vibrational.